2017
DOI: 10.1007/s12016-017-8602-y
|View full text |Cite
|
Sign up to set email alerts
|

Cypress Pollinosis: from Tree to Clinic

Abstract: Cypress (Cupressus sp.pl) is a genus within the Cupressaceae family. This family covers all of the Earth's continents except for Antarctica, and it includes about 160 species. The most important taxa for allergic diseases belong to five different genera: Cupressus, Hesperocyparis, Juniperus, Cryptomeria, and Chamaecyparis. Cupressaceae species share a common pollen type that can even include the genus Taxus (Taxaceae) when this plant is also present. As Juniperus oxycedrus pollinates in October, Cupressus semp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 157 publications
0
44
1
2
Order By: Relevance
“…Similarly, little is known about allergen(s) other than Pru p 7 potentially involved in the cypress‐peach syndrome . Teams from southern France and Spain reported an association of CP and PA in Pru p 3 sensitized patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, little is known about allergen(s) other than Pru p 7 potentially involved in the cypress‐peach syndrome . Teams from southern France and Spain reported an association of CP and PA in Pru p 3 sensitized patients .…”
Section: Discussionmentioning
confidence: 99%
“…Although cypress trees are typical of Mediterranean regions, Cupressaceae pollen dispersal also affects non‐Mediterranean environments, including Central Europe, North America, Mexico and Japan . GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The pollinosis can be severe including infectious complications, partly due to winter pathologies occurring within cypress pollinating period. 2 In Southern France, a pollen food-associated syndrome (PFAS) was described involving cypress pollen and peach and/or citrus sensitizations inducing mainly oral syndrome but also urticaria and angioedema.…”
Section: To the Editormentioning
confidence: 99%
“…Because Pru p 7 shares more than 80% sequence identity with snakin-1 and more than 95% with other fruit GRP allergens, BP14 should be considered as the cross-reactive allergen in the 2 documented PFAS involving peach and/or citrus. 1 Preliminary experiments showed that patients allergic to cypress pollen and citrus expressed IgE against cypress pollen BP14 cross-reactive with a cationic 12-kDa allergen from grapefruit (unpublished data Q 1 ). Therefore, snakin/GRP may represent a new diagnostic marker of PFAS in addition to other allergens such as Bet v 1-like proteins involved in the well-studied birch/apple syndrome.…”
Section: To the Editormentioning
confidence: 99%